Rancang Bangun Turbin Angin Sumbu Horizontal Dengan Tipe Bilah Inverse Taper Berbahan Dasar Komposit Serat Tandan Kosong Sawit - Damanik, Reinhard Parulian; Agustina, Dinni; Martin, Awaludin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Overcome the use of fossil fuel based power plants is improving annually and waste in Indonesia palm that cannot be used again, it is the basis for this research through the planning and manufacturing of wind turbine blades of elementary substance composite fibers of empty palm. As for the wind turbine blades designed to be adapted for areas with low wind speeds, the blade is made with an inverse taper type that can convert wind energy into a rotor round with a large torque. The type of airfoil used is NACA 4415 with increasing the chord thickness percentage by 30%. The result of the calculation, obtained radius blade 1,1m and hub 0,2m with the number of blades 5. In the making of blades, the fibre of empty palm is given alkaline treatment with a 3% NaOH rate of 2 hours. Composites made with 5% fiber content of epoxy resin with the length of fiber used is 30mm. Based on the aerodynamic simulation results using Qblade applications, the blade can generate 318W of power at 7m/s wind speeds with blade rotation speed 120rpm. Keyword: Inverse Taper, Fibre Bunch of Empty Palm